CO2 Laser Marsupialization for Internal and Combined Laryngocele - Verro, Barbara; Saraniti, Carmelo (International Archives of Otorhinolaryngology, 2023)
Introduction Laryngocele is an air-filled dilatation of the laryngeal saccule that can be classified according to its extent (internal, external, or combined) and contents (laryngocele or laryngopyocele). To date, there is no consensus on the best treatment for laryngocele.Objective The present study aims to demonstrate for the first time the effectiveness of CO2 laser marsupialization for internal and combined laryngoceles.Methods A retrospective study was accomplished in our ENT Clinic of the University Hospital, from 2010 to today, recruiting patients according to strict criteria. All patients had internal or combined laryngocele/laryngopyocele treated with CO2 laser marsupialization.Results A total of 15 patients were enrolled for a total of 17 laryngoceles; 66.67% of the patients were males and the mean age was 54.4 (±14.12) years old. Internal laryngoceles accounted for 64.71% of the total, and only 7 cases were laryngopyoceles. At the 3-year follow-up, no signs of recurrence were found.Conclusion CO2 laser marsupialization is efficacious in the treatment of laryngocele or laryngopyocele, both internal and combined, in terms of efficiency, safety, and fast postoperative recovery, without need for tracheotomy or open surgery.
Keywords: laryngocele; laser surgery; laser therapy; therapeutics